Lipoma of the corpus callosum: Fat in the brain - Thapa, Ashish Jung (Nepal Journal of Neuroscience, 2021)
Intracranial lipomas are very rare, slow-growing, and benign tumors usually asymptomatic but occasionally associated with symptoms like a seizure. This rare occurrence is usually diagnosed incidentally and magnetic resonance imaging is the choice of investigation and diagnosis can be confirmed with fat suppression sequences. Management of corpus callosal lipoma is mainly conservative management with surgery not indicated due to the location and its peripheral structures. Managing seizure is the mainstay of the treatment. We present a case of incidentally diagnosed tubulonodular corpus callosal lipoma after having an event of a fall injury.